La defensa de la competencia como palanca para una contratación pública íntegra y alineada con el cumplimiento normativo - Urresola Clavero, Alba (2022)
In any country in the world, public procurement is the area in which governments not only carry out a significant percentage of public spending, but also serves to promote and develop public policies in such a way that it becomes a launching pad for a country’s social and economic objectives.Throughout the four generations of procurement directives, the European Union has focused on this goal: to turn public procurement into one of the integrating mechanisms of the internal market and, to this end, the procedures and rules governing this procurement system must respect the freedoms of the Treaty on the Functioning of the European Union (TFEU): the free movement of goods, freedom of establishment and freedom to provide services, but also the principles derived from these, i.e. equal treatment, non-discrimination, mutual recognition, proportionality and transparency.The European Union’s public procurement policy is a fundamental pillar for the consolidation of the internal market and also a tool for the rationalization of spending and public funds in order to achieve a sustainable system.The latest procurement directives, the so-called fourth generation directives, and more specifically Directive 2014/24/EU, of the European Parliament and of the Council, of 26 February 2014, was implemented in the Spanish legal system through the current Law 9/2017, of 8 November, on Public Sector Contracts (LCSP), a law that faithfully internalizes the relevance of procurement in the development of public policies and the achievement of its objectives. It is a law that consolidates the strategic vision of public procurement, accentuating the spirit of regulatory compliance that must preside over public action. Thus, the current LCSP focuses not only on what is purchased but also on how it is purchased.Section III of the Preamble of the LCSP refers to a legal system of public procurement. It is therefore a complex regulation that seeks open procurement at the European level, which is accessible to small and medium-sized companies. To this end, priority is given to safeguarding competition, a principle that acquires greater prominence than in previous regulations, being one of the main priorities not only in the substantive regulation but also in the established institutional scheme.In addition, the current Spanish and European regulations go a step further by placing at the center of the rules governing public procurement, not only the classic principles mentioned above (equality, non-discrimination, proportionality, etc.), but also a new principle, that of integrity, which until now was considered a moral value, but which becomes in the current LCSP a new transversal and integrating principle of the spirit that should govern public procurement. Thus, the LCSP is equipped, among others, with different mechanisms aimed at guaranteeing the integrity of the contracting authorities, based on free competition and, if necessary, on the intervention of the competition authorities. These mechanisms are aimed at ensuring compliance by public actors and are complemented by other tools aimed at verifying the legality of the actions of bidders; in short, these mechanisms and tools are aimed at promoting compliance with the regulations with the ultimate goal of guaranteeing integrity in the field of public procurement.Thus, the defense of competition is presented as a crucial instrument to ensure integrity, and as an indispensable value for an egalitarian procurement, open to the European market, accessible to small and medium enterprises and, ultimately, a more integral procurement and focused on compliance. For all these reasons, competition compliance is a tool that should be promoted by contracting authorities in their contractual practice, as well as by companies that participate in public procurement processes and that, given that they aspire to a business management with integrity, should advocate the development of their compliance programs also in the area of competition.